2004
DOI: 10.1081/iph-200026914
|View full text |Cite
|
Sign up to set email alerts
|

Myelopoietic Response in Mice Exposed to Acute Cold/Restraint Stress: Modulation by Chlorella vulgaris Prophylactic Treatment

Abstract: In this study, hematopoietic cells from mice pretreated with CVE and exposed to acute cold/restraint stress were stimulated in the presence of growth factors to form colonies, thus providing accurate information about the modulation of the green algae of the stress-induced changes in the hematopoietic response. Our results demonstrated that exposure to acute stress affected hematopoiesis. Mice exposed for a 2.5-hour time period of cold and restraint presented diminished clonal capacity for CFU-GM content per f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
1
13
0
8
Order By: Relevance
“…Of importance, Chlorella also increased CSA in control group (p<0.05). This effect of the alga was consistent with our previous studies using different experimental models [11,26,30,32,33].…”
Section: Serum Colony-stimulating Activity (Csa) In Obese Micesupporting
confidence: 81%
See 2 more Smart Citations
“…Of importance, Chlorella also increased CSA in control group (p<0.05). This effect of the alga was consistent with our previous studies using different experimental models [11,26,30,32,33].…”
Section: Serum Colony-stimulating Activity (Csa) In Obese Micesupporting
confidence: 81%
“…These results demonstrated that Chlorella up-regulates the production of colony-stimulating factors in the same manner as for CFU-GM, leading to appropriate production Extramedular Hematopoiesis in the Spleen of Obese Mice Modulation by the Alga Chlorella and efficient mobilization of early immune cells, which are crucial to the performance of the surveillance as well as the effector functions of the immune system. Importantly, the ability of the alga to reverse both the myelosuppression and the splenic EMH was related to its ability to recover the homeostasis [7,11,26,30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of reports focus on adrenergic and monoaminergic response and those specifically addressing myelopoiesis, finding diminished CFU-GM populations [19-22,24] without addressing the effects of psychological stress on erythroid development. Here we employed clinical, laboratory and genomic analysis of a murine model of chronic restraint stress (RST) to examine the effects of chronic psychological stress on erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint stress, an experimental model of psychological stress 5, affects different physiological processes including haematopoiesis 6. Accordingly, Sherstoboev and Minakova showed an expansion of erythroid progenitors in the bone marrow during chronic stress 7.…”
Section: Introductionmentioning
confidence: 99%